Математичне моделювання механотермодифузійних процесів у твердих розчинах при врахуванні локального зміщення маси - Бурак, Я.Й.; Кондрат, В.Ф.; Грицина, О.Р. (Видавничий дім "Академперіодика" НАН України, 2007)
With the use of the methods of mechanics of solids and nonequilibrium thermodynamics, the mechanothermodiffusion model of isotropic n-component solid solution is proposed taking into account the local displacement of a mass. It is shown that this approach results in expanding the state parameters space, redefining the stress tensor, and the occurrence of additional volume forces.